Development of Evaluation Models for Surface-to-Air Missile Firing Effectiveness with Consideration of Air Target Kill Probabilities - Openko, Pavlo; Piavchuk, Oleksandr; Tselischev, Yurii; Kudriashov, Viktor; Kolomiitsev, Oleksii; Voinov, Valerii (Social Development and Security, 2025)
Purpose. To develop a partial model for calculating the values of conditional probabilities of target engagement, to generate optimal options for countering enemy air strikes, and to justify the general directions for improving elements of the fire control system. Method. The main research methods are: statistical analysis, numerical methods, and comparative analysis. Findings. А relationship is presented between the values of conditional probabilities of target engagement and nine key parameters that characterize surface-to-air missile firing and fire control. The practical results obtained from the partial model are essential for the effective employment of weapon systems as intended. Theoretical implications. The article provides calculations that make it possible to pre-plan several courses of action for self-propelled fire units (combat vehicles) and subunits in repelling enemy air strikes. The model takes into account the parameters of the enemy air strike against the combat formations of friendly forces. Currently, there is no existing partial model that determines the effectiveness of missile firing while considering the probabilities of air targets entering the target allocation zone. The study also includes an assessment of the probability that air targets will not exit the missile launch and engagement zones of the surface-to-air missile system after launch. This assessment considers factors such as the effective radar cross-section (RCS) of targets, the level of jamming, and target overload during maneuvering. Therefore, the task of developing response options for self-propelled fire units and subunits in countering enemy strikes is both important and timely.